Study on morphological traits, nutrient compositions and comparative metabolomics of diploid and tetraploid Tartary buckwheat sprouts during sprouting. (February 2023) - Liu, Changying; You, Xiaoqing; Qiu, Qingcheng; Ye, Xueling; Wu, Qi; Wan, Yan; Jiang, Liangzhen; Wu, Xiaoyong; Sun, Yanxia; Huang, Jingwei; Fan, Yu; Peng, Lianxin; et al.
Graphical abstract: Highlights: Chromosome doubling changed morphology, nutrition and metabolome of TB sprouts. Tetraploid sprouts had higher biomass, thicker hypocotyl, and more ash and minerals contents. 62 diseases-resistance metabolites and 43 key active ingredients were identified in TB sprouts. 209 metabolites were regulated by chromosome doubling including some key bioactive metabolites. Abstract: Tartary buckwheat (TB) sprout is a kind of novel nutritional vegetable, but its consumption was limited by low biomass and thin hypocotyl. The tetraploid TB sprouts was considered to be able to solve this issue. However, the nutritional quality of tetraploid TB sprouts and differences between conventional (diploid) and tetraploid TB sprouts remain unclear. In this study, the morphological traits, nutrient compositions and metabolome changes of diploid and tetraploid TB sprouts were analyzed. The water, pigments and minerals contents of TB sprouts increased during sprouting, while the contents of total soluble protein, reducing sugar, cellulose, and total phenol decreased. Compared with diploid sprouts, tetraploid sprouts had higher biomass and thicker hypocotyl. Tetraploid sprouts had higher ash and carotenoid contents, but had lower phenol and flavonoid accumulation. 677 metabolites were identified in TB sprouts by UPLC-MS analysis, including 62 diseases-resistance metabolites and 43 key active ingredients. Some key bioactive metabolites, such as rimonabant, quinapril, 1-deoxynojirimycin and miglitol, were identified. 562 differential expressed metabolites (DEMs) were identified during sprouting with seven accumulation patterns, and five hormones were found to be involved in sprout development. Additionally, 209 DEMs between diploid and tetraploid sprouts were found, and some key bioactive metabolites were induced by chromosome doubling such as mesoridazine, amaralin, atractyloside A, rhamnetin and Qing Hau Sau. This work lays a basis for the development and utilization of TB sprouts and provides evidence for the selection of tetraploid varieties to produce sprouts with high biomass and quality.